Preferences for Restorative Landscape Elements among the University Students in Bogor City Parks by Using Visitor - Employed Photography - Prita Indah Pratiwi; Bambang Sulistyantara; Aditya Aji Pamungkas (School of Postgraduate Studies, Diponegoro Univer, 2026)
City parks are designed to serve various community needs, ranging from social and cultural functions to economic purposes, and they can even improve physical and mental health. In West Java, mental health issues are a concern experienced by age groups over 75 years as well as those between 15 and 24 years. Among these, university students face a particularly high level of mental health disorders, especially academic anxiety. To address this, the present study aims to: (1) identify landscape views in Bogor City Square, Sempur Park, and Heulang Park based on geotagged photos; (2) classify restorative landscape elements; and (3) evaluate the effects of restoration on university students. This was accomplished through an experimental method involving direct observation and the completion of the Perceived Restorativeness Scale (PRS) questionnaire. Parameters observed included landscape views, park elements, and restorative effects. For the experiment, 30 university students walked around the park for 15 minutes. Analyses included spatial analysis of photo distribution in QGIS, content analysis of photos using the Google Cloud Vision API, and analysis of restorative effects. The results indicate the following: first, there are 1 to 3 hotspots with the highest photo density in the three parks; second, restorative landscape elements include plants (1445 keywords), trees (1099 keywords), and grass (853 keywords); and third, Heulang Park achieves the highest restorative scores compared to the other two parks (being away = 4.3, fascination = 4.3, coherence = 3.3, compatibility = 4). Overall, this study uses cloud technology to conduct a preliminary research of the restorative effects for the users in Bogor city parks analyzing geotag information.